The Role of Sensitivity to Reward and Punishment in Aggression - Megías-Robles, Alberto (Journal of interpersonal violence, 2022)
The study of the risk and protective factors in aggression is of fundamental importance for our society. The aim of this research was to clarify the role of sensitivity to reward/punishment in aggression and provide a better understanding of the mechanisms underlying this relationship, particularly given that previous studies in the literature have yielded mixed results. To this end, two studies were conducted. In Study 1 (484 participants; Mage = 39.09; 48.6s women), we explored the relationship between sensitivity to reward and punishment and four components of aggression: physical, verbal, anger, and hostility. In Study 2 (229 participants; Mage = 21.52; 56.77% women), we investigated the moderating role of emotion regulation ability in this relationship. The findings of Studies 1 and 2 supported the existence of a positive relationship between sensitivity to reward and aggression, that is, a high reactivity to reward acted as a risk factor. With respect to sensitivity to punishment, mediation analysis revealed that this variable may act both as a protective factor as well as a risk factor for behavioral aggression. A higher reactivity to punishment had a direct negative effect on physical and verbal aggression, inhibiting aggressive behavior. However, a higher reactivity to punishment also implied a positive indirect effect on physical and verbal aggression through an increase in anger and hostility. Interestingly, Study 2 revealed that these indirect effects were moderated by emotion regulation ability. Our results could help to inform the design of aggression prevention and intervention programs for reducing the impact of this behavior on our society.